2008
DOI: 10.1177/1087054708322996
|View full text |Cite
|
Sign up to set email alerts
|

Do Attention Deficits Influence IQ Assessment in Children and Adolescents With ADHD?

Abstract: The associations between IQ and attention deficits in ADHD are generally modest, with the mean influence on IQ probably amounting to 2 to 5 IQ points. This may serve as a benchmark when clinicians interpret the validity of IQ in this clinical population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 45 publications
8
54
2
2
Order By: Relevance
“…This is consistent with a study assessing the relationship between WISC-III IQ scores (FSIQ, VIQ, and PIQ) and the severity of attention deficits, which found that FSIQ and PIQ might be more strongly related to inattention in ADHD than was VIQ (Jepsen et al 2009). It has been commonly assumed that language based reasoning (Verbal IQ, VIQ) is mediated primarily by the left hemisphere and nonverbal reasoning (Performance IQ, PIQ) is mediated by the right hemisphere (Blackburn et al 2007).…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with a study assessing the relationship between WISC-III IQ scores (FSIQ, VIQ, and PIQ) and the severity of attention deficits, which found that FSIQ and PIQ might be more strongly related to inattention in ADHD than was VIQ (Jepsen et al 2009). It has been commonly assumed that language based reasoning (Verbal IQ, VIQ) is mediated primarily by the left hemisphere and nonverbal reasoning (Performance IQ, PIQ) is mediated by the right hemisphere (Blackburn et al 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Performance on IQ tests has been associated with and also partly explained by other aspects of neurocognitive function (Adolfsdottir, Sørensen, & Lundervold, 2008;Tillman, Bohlin, Sørensen, & Lundervold, 2009). More recent studies have more consistently reported low to moderate correlations between IQ and performance on neurocognitive tests in children and adolescents with ADHD (Jepsen et al, 2009), and that also ADHD symptoms (e.g., Bezdjian, Baker, Lozano, & Raine, 2009) and symptoms associated with affective disorders (Nigg & Casey, 2005;Sobanski et al, 2010;Sørensen, Plessen, Nicholas, & Lundervold, 2011) are crucial to understand characteristics of cognition in children. Associations between intellectual and neurocognitive function have also been demonstrated in children with ASD where the most distinguishing feature of intellectual function seems to be an uneven rather than low function (Cederlund & Gillberg, 2004;Gilchrist, Green, Cox, Burton, Rutter, & Couteur, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between measures of IQ and attention have been widely investigated in studies of children with ADHD. In a review, Jepsen et al (2009) concluded that the influence of IQ on attention and visa versa was best described as rather small. Studies of ASD have indicted a stronger influence of IQ on attention (and on everyday functioning in more general terms; Liss et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion drawn from this study was similar to former studies. 18 In that, it is important to clarify that the IQ score changes observed in the intervention group should not be considered as an indicator that these children became more intelligent or that stimulant can elevate children's intellectual ability. Although we did find an increase in scores from children after receiving methylphenidate, the most probable explanation is that the advancement was due to a change in test-taking behavior, and thus, the changes in IQ scores were an indirect benefit from taking the medication.…”
Section: Discussionmentioning
confidence: 99%